2022
DOI: 10.1097/md.0000000000028680
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of sarcopenia in patients with hepatocellular carcinoma treated with lenvatinib

Abstract: Our study investigated the correlation between sarcopenia and clinical outcomes in patients with hepatocellular carcinoma (HCC) treated with lenvatinib. We retrospectively evaluated 40 consecutive patients with unresectable HCC receiving lenvatinib between November 2018 and May 2020 at the First Hospital of Jilin University. Skeletal muscle mass was measured before treatment initiation. Prognostic significance was assessed with univariate and multivariate Cox proportional hazards models. Overall survival (OS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 53 publications
0
33
1
Order By: Relevance
“…A total of 2435 studies were identified after screening the databases, from which 1867 studies were excluded, followed by reviewing the abstracts of 568 studies in accordance with the inclusion criteria. Finally, 57 studies 3 , 21 76 were included in this meta-analysis after detailed full-text examination (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2435 studies were identified after screening the databases, from which 1867 studies were excluded, followed by reviewing the abstracts of 568 studies in accordance with the inclusion criteria. Finally, 57 studies 3 , 21 76 were included in this meta-analysis after detailed full-text examination (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 57 studies involving 9790 HCC patients were included in the meta-analysis. The studies were conducted in different regions, with 41 studies 3 , 24 , 26 28 , 32 37 , 39 41 , 43 51 , 54 60 , 62 , 63 , 66 69 , 71 , 73 76 (Japan provided the largest volume of studies, followed by the South Korea) from Asia, and 16 studies 21 23 , 25 , 29 31 , 38 , 42 , 52 , 53 , 61 , 64 , 65 , 70 , 72 conducted in non-Asia regions. The enrolled patients covered all stages of HCC (from BCLC stage 0/A to BCLC stage D) and the corresponding treatments (RFA, hepatectomy, LDLT, TACE, TARE, radiotherapy, sorafenib, lenvatinib, and ICIs).…”
Section: Resultsmentioning
confidence: 99%
“…SMI is the most widely used index and sarcopenia is defined as SMI < 42 cm 2 /m 2 for men and <38 cm 2 /m 2 for women based on the guideline proposed by Japan Society of Hepatology (JSH) ( 61 ). Among twenty-seven studies using SMI, eight studies used the cut-points proposed by JSH ( 14 , 22 , 32 , 35 , 42 , 45 , 49 , 52 ), six studies employed the Martin cut-points ( 41 , 53 , 55 , 57 , 58 , 60 ), four studies applied the Vledder cut-points ( 27 , 28 , 34 , 38 ), and their own cut-points were measured in other studies. HR was estimated by univariate and multivariate Cox proportional hazards regression to investigate the influence of sarcopenia on OS and/or PFS of HCC patients in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the moderate risk of bias was determined to be due to study attrition in eight studies, adjustment for other prognostic factors in eight studies, statistical analysis and reporting in five studies. In general, of the 42 included studies, 34 studies were at an overall low risk of bias ( 14 16 , 22 25 , 28 32 , 34 , 35 , 37 , 39 44 , 46 , 47 , 49 59 ), while eight were at an overall moderate risk of bias ( 26 , 27 , 33 , 36 , 38 , 45 , 48 , 60 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation